Tissue Engineered Axon Tracts Serve as Living Scaffolds to Accelerate Axonal Regeneration and Functional Recovery Following Peripheral Nerve Injury in Rats - Katiyar, Kritika S.; Struzyna, Laura A.; Morand, Joseph P.; Burrell, Justin C.; Clements, Basak; Laimo, Franco A.; Browne, Kevin D.; Kohn, Joachim; Ali, Zarina; Ledebur, Harry C.; Smith, Douglas H.; Cullen, D. Kacy (Frontiers in Bioengineering and Biotechnology, 2020)
Strategies to accelerate the rate of axon regeneration would improve functional recovery following peripheral nerve injury, in particular for cases involving segmental nerve defects. We are advancing tissue engineered nerve grafts (TENGs) comprised of long, aligned, centimeter-scale axon tracts developed by the controlled process of axon “stretch-growth” in custom mechanobioreactors. The current study used a rat sciatic nerve model to investigate the mechanisms of axon regeneration across nerve gaps bridged by TENGs as well as the extent of functional recovery compared to nerve guidance tubes (NGT) or autografts. We established that host axon growth occurred directly along TENG axons, which mimicked the action of “pioneer” axons during development by providing directed cues for accelerated outgrowth. Indeed, axon regeneration rates across TENGs were 3-4 fold faster than NGTs and equivalent to autografts. The infiltration of host Schwann cells – traditional drivers of peripheral axon regeneration – was also accelerated and progressed directly along TENG axons. Moreover, TENG repairs resulted functional recovery levels equivalent to autografts, with both several-fold superior to NGTs. These findings demonstrate that engineered axon tracts serve as “living scaffolds” to guide host axon outgrowth by a new mechanism – which we term “axon-facilitated axon regeneration” – that leads to enhanced functional recovery.